2020
DOI: 10.1038/s41598-020-66606-5
|View full text |Cite
|
Sign up to set email alerts
|

Disorganized Attachment pattern affects the perception of Affective Touch

Abstract: Touch, such as affective caress, can be interpreted as being pleasant. The emotional valence that is assigned to touch is related to certain bottom-up factors, such as the optimal activation of C-tactile (CT) afferents. Tactile processing with a hedonic or emotional component has been defined as affective touch-a component that CT fibers are likely to convey. Tactile deficiencies are frequent in the psychiatric population but also in healthy people with disorganized attachment; accordingly, it is likely that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…Indeed, it is well-known that inter-subject differences are certainly a crucial aspect when studying interoception, which is based on participant's inner sense [57] and may become even more relevant in case of hedonic haptic contact [58,59]. Previous work has shown that other factors, such as autistic traits [18,60] (for a different perspective see [61,62]), motivational states [63], attachment style [64,65], sex [66], and behavioral inhibition system sensitivity [59] modulate affective touch. In support of this perspective, it is worth underlying that the general experience of touch-and not specifically the affective one-entails different brain responses among individuals even when tactile expectancy and attentional level are carefully taken under control [67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is well-known that inter-subject differences are certainly a crucial aspect when studying interoception, which is based on participant's inner sense [57] and may become even more relevant in case of hedonic haptic contact [58,59]. Previous work has shown that other factors, such as autistic traits [18,60] (for a different perspective see [61,62]), motivational states [63], attachment style [64,65], sex [66], and behavioral inhibition system sensitivity [59] modulate affective touch. In support of this perspective, it is worth underlying that the general experience of touch-and not specifically the affective one-entails different brain responses among individuals even when tactile expectancy and attentional level are carefully taken under control [67].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the new scientific evidence given by our study, it is not immune from some limitations. First of all, when selecting the neutral touch, we opted for a slower stroking (18 cm/sec) (for a similar procedure, see: [14,17,23,25,26,90,91]) compared to that mostly used in the literature (30 cm/sec) (for a similar procedure, see: [4,5,7,12,16,[31][32][33]65] as the counterpart of the pleasant stimulation). The reduced experimental evidence about the haptic stimulation delivered at such velocity could have somehow impacted our data.…”
Section: Limitationsmentioning
confidence: 99%
“…Though not specific to tactile interactions, a longitudinal study showed higher caregiver nurturance at age 3 was associated with declines in attachment avoidance in adolescent in young adults [ 65 ]. Recently, Spitoni and collaborators [ 49 ] experimentally showed that attachment patterns affect the perception of affective touch in adults. They examined whether people with disorganized attachment (scores that were related to experiences of loss, abuse, or both regarding primary caregivers) perceived affective touch as being less pleasant than those with organized attachment.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors later showed in an experimental setting that attachment anxiety affected discrimination in self-reported pleasantness between affective and non-affective touch, with increasing levels of attachment anxiety leading to a decrease discrimination between conditions [ 48 ]. In a recent study Spitoni et al [ 49 ] analysed whether the perception of affective touch differed between adults with different attachment patterns. In contrast with adults with an organized attachment pattern, those with disorganized attachment did not perceive affective touch as pleasant, showing preference for non-affective touch.…”
Section: Introductionmentioning
confidence: 99%
“…There are 36 items in the questionnaire, which are scored on a scale of 1 to 4. The reliability and validity of the questionnaire are good, with Cronbach's α coefficient of 0.70 and half reliability of 0.64 [7].…”
Section: Methodsmentioning
confidence: 97%